A command to estimate and interpret models of dynamic compositional dependent variables: New features for dynsimpie. (September 2020) - Jung, Yoo Sun; Souza, Flávio D. S.; Philips, Andrew Q.; Rutherford, Amanda; Whitten, Guy D.
Philips, Rutherford, and Whitten (2016, Stata Journal 16: 662–677) introduceddynsimpie, a command to examine dynamic compositional dependent variables. In this article, we present an update todynsimpie and three new adofiles:cfbplot, effectsplot, anddynsimpiecoef . These updates greatly enhance the range of models that can be estimated and the ways in which model results can now be presented. The commanddynsimpie has been updated so that users can obtain both prediction plots and change-from-baseline plots using postestimation commands. With the new commanddynsimpiecoef, various types of coefficient plots can also be obtained. We illustrate these improvements using monthly data on support for political parties in the United Kingdom.